2014
DOI: 10.1111/jph.12334
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biological Analysis of Potato virus M (PVM) Isolates from the Czech Republic

Abstract: The sequences of the 3′‐terminal region of four Czech Potato virus M isolates VIRUBRA 4/007, VIRUBRA 4/009, VIRUBRA 4/016 and VIRUBRA 4/035 were determined and compared with sequences of PVM isolates available in GenBank. Among the Czech isolates, VIRUBRA 4/007 and 4/016 as well as VIRUBRA 4/016 and 4/035 showed the highest nucleotide identity (93%). Isolates VIRUBRA 4/007, 4/016 and 4/035 were most similar to the PV0273 isolate from Germany and to the wild isolate from Russia. Interestingly, isolate VIRUBRA 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…PVM-O isolates are reported from several EU MSs, i.e. Czech Republic, Germany, Latvia, Poland and Slovakia (Plchova et al, 2015;Glasa et al, 2019;He et al, 2019).…”
Section: Pest Distribution In the Eumentioning
confidence: 99%
See 2 more Smart Citations
“…PVM-O isolates are reported from several EU MSs, i.e. Czech Republic, Germany, Latvia, Poland and Slovakia (Plchova et al, 2015;Glasa et al, 2019;He et al, 2019).…”
Section: Pest Distribution In the Eumentioning
confidence: 99%
“…Unlike many other viruses, these two strains have recently been distinguished and there was no prior discrimination of these strains based on biological properties. There is evidence for the existence of genetic variation within these strains, in particular within PVM-D (Cavileer et al, 1998;Xu et al, 2010;Tabasinejad et al, 2014;Plchova et al, 2015;Su et al, 2017;He et al, 2019).…”
Section: Intraspecific Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that members of Carlavirus such as PVS, PVM, and hop mosaic virus (HpMV) shown remarkable genetic diversity in their population (Cox and Jones, 2010;Poke et al, 2010;Xu et al, 2010;Salari et al, 2011;Tabasinejad et al, 2014;Plchova et al, 2015). The genetic diversity of PVM has been well studied for the isolates of China and Iran that classified the PVM isolates into two clades: PVM-ordinary (PVM-o) and PVM-divergent (PVM-d) (Tabasinejad et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Later, Tabasinejad et al (2014) named these two major clades PVM-ordinary (PVM-o) and PVM-divergent (PVM-d), respectively. It was shown that potato isolates of PVM from Iran and Czech Republic are located within both clades (Tabasinejad et al, 2014;Plchova et al, 2015). This suggests that the geographical origin is not the only determining factor of the phylogenetic divergence of PVM isolates into two main clades.…”
Section: Introductionmentioning
confidence: 99%